Association of polymorphisms in ADAMTS-5 gene with the susceptibility to knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 49 (10th December 2021) - Deng, Tingting; Zhou, Yue; Zhang, Kaixin; Dong, Zhibin; Zhang, Jingwen; Lv, Xinwei; Song, Shuai; Ma, Yuxia
Abstract: Background: To systematically review literature evidence to discover the association of ADAMTS5 (A Disintegrin And Metalloproteinase with Thrombospondin-like motifs 5) gene polymorphisms and the risk of developing KOA (knee osteoarthritis). Methods: We systematically searched the related randomized controlled trials in 4 databases from inception to August 2021, including the Embase, Web of Science, PubMed, and CNKI (Chinese National Knowledge Infrastructure) databases. No language and publication status restrictions. Two reviewers will independently screen all included studies, and the meta-analysis will be conducted using the Review Manager (RevMan 5.3, Cochrane Collaboration, Nordic Cochrane Center, Copenhagen, Denmark). Results: The gathered evidence suggests that there may be a close relationship between the SNP in the ADAMTS5 gene and KOA development. This study will provide a high-quality and convincing evaluation of the treatment of KOA from the consideration of ADAMTS5 gene and will be published in a peer-reviewed journal. Conclusion: ADAMTS5 polymorphism is likely an important risk factor for the development of KOA. Our study will provide a more accurate treatment method for the treatment of KOA. Trial registration number: CRD42021276317